The Impact of Firm Value on Capital Structure, Profitability, and Firm Size - Sri Yuli Waryati; Fathonah Eka Susanti; Sarastuti Wahyuningrum (Cita Konsultindo Research Center, 2022)
The purpose of this study is to determine the impact of capital structure, profitability, and firm size on firm value. The population of this study was 181 companies in the manufacturing sector, from which samples were taken using the purposive sampling method to obtain 77 sample companies for 4 years of observation from 2016 to 2019 with 308 observations. The research data came from sample companies downloaded from the Indonesia Stock Exchange's website. The research method employed is the classical assumption test in the form of a multicollinearity and heteroscedasticity test, as well as a multiple regression analysis of panel data with a fixed effect test that has been declared feasible (goodness of fit). According to the findings of this study, capital structure, profitability, and firm size all have a significant positive effect on firm value.Keywords: Capital Structure, Profitability, Firm Size, Firm Value